THE IMPACT OF DOMESTIC COMPOSTING IN A COMMUNITY IN THE MUNICIPALITY OF CODÓ (MA) - Sales, Jailson Pinheiro Silva de (2021)
Composting is the process of transforming organic matter into fertilizer, which has environmental and economic benefits. This study aimed to promote composting in a community in the municipality of Codó (MA) as an alternative for the reduction of household waste and the adoption of healthier lifestyle habits. This is a field research with the application of questionnaires to assess the socio-environmental perception of students and residents of the community around the school, in addition to giving lectures and workshops for the construction of domestic composters. In this sense, 40% of the participants consider garbage as the main environmental problem in the municipality; 62.5% were unaware of composting; and 65% of the participants built a domestic composter and started using it. As for changes in habits, 52.5% reported that they rethought their disposal habits, implying that composting could stimulate the development of healthier living habits and reduction of waste.